Ciudadanía, visibilidad y multiculturalismo con respecto a lo afro en Santa Marta, Caribe colombiano - Benei, Véronique (2018)
In several writings on political science, political philosophy, history and political anthropology, the question of visibility has acquired centrality in the debates related to multicultural citizenship. This article purports to illuminate some of the processes of cultural construction at stake in Caribbean Colombia today. In the first instance borrowing from the evolutionary model of citizenship proposed by T.H. Marshall in which the cultural phase turns out to be the last of a chain of claims towards recognition by the nation-state, I later argue that this framework nonetheless continues to reproduce and obscures a phenomenological primacy inherent in the derivative conception of political modernity, wherein the sense of sight - and the resulting political term of “visibility” has become the one and only mode of categorization. In this article, I intend to demonstrate how the case of the production of a form of cultural citizenship through “Afro” identifications in Caribbean Colombia today both interrupts this phenomenological-political chain, and allows us to imagine other sensory modalities forming an integral part of a “multicultural” citizenship practice.